National memory: memorial objects to the fallen soldiers of the Great Patriotic War of 1941–1945. Spassky municipal district of Nizhny Novgorod region - Kutina E. P. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
the article presents research on the history of the creation of monuments to the fallen soldiers of the Great Patriotic War of 1941–1945 in the Spassky district. Reliable information has been disclosed on how the creation, opening of monuments to fallen soldiers and their further condition took place. The important role of the memory of the people in the patriotic education of young people through memorials is indicated.
Keywords: история; history; Великая Отечественная война 1941–1945 гг; патриотическое воспитание молодежи; patriotic education of youth; the Great Patriotic War of 1941–1945; память народа; мемориалы; памятники; memory of the people; memorials; monuments